ANALISIS HAMBATAN KAPAL DENGAN VARIASI STEP HULL MENGGUNAKAN METODE CFD - Muhammad Rianza (2023)
A step hull is a hull design or shape that has steps or center piles at its bottom. These piles usually consist of flat piles separated by vertical or angled steps. This shape can be found on ships designed to improve speed, performance and efficiency. The purpose of this study is to identify the effect between variations in the size and number of step hulls on the resistance of step hull vessels. This research utilizes the CFD method and there are 3 hull configurations. The results of this study reveal that the step hull model with the number of step hulls of 2 levels, and having a length of 15%L and 27%L and a step height of 60 mm at each step has the lowest drag compared to other variations with a comparison with a ship using a variation of 11%Ls 30mmHs by 25%. This study concludes that changing the shape of the step on the hull will affect the resistance received by the ship. Thus, this research can provide an understanding of the step hull and become material in the development of the step hull.